Analisis Outcome Terapi Amikasin Terhadap Penurunan Sesak Nafas Pada Pneumonia Pediatrik di Instalasi Rawat Inap RSUD Arifin Achmad Provinsi Riau - Muharni, Septi; Sulastri; Agistia, Nesa; Husnawati; Aryani, Fina; Djohari, Meiriza (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Amikacin is one of the aminoglycoside antibiotics that is bactericid and is included in the narrow therapeutic index group. The use of antibiotics must be appropriate in order to achieve maximum therapeutic outcome. This study aims to determine the correlation of the use of amikacin antibiotics to the achievement of therapeutic outcomes for reducing shortness of breath in pediatric pneumonia in Arifin Achmad Hospital, Riau Province. This research is observational research descriptive analitic coss sectrional on 20 medical records of patients pneumonia pediatric. Based on the analysis of the correlation between gender and age range, it has moderate and insignificant correlation with the outcome of amikacin therapy (r = 0.404 and p value = 0.143), (r = 0.452 and p value = 0.274) and the severity of breathing towards the therapeutic outcome of using amikacin was strongly correlated and significant (r = 0.675; P = 0.002). These results indicate that the use of amikacin changes the therapeutic outcome and the therapeutic outcome is influenced by the severity of the patient's breathing